Selected areas in cryptography – SAC 2017 : 24th International Conference, Ottawa, ON, Canada, August 16-18, 2017, Revised selected papers /: 24th International Conference, Ottawa, ON, Canada, August 16-18, 2017, Revised selected papers. (2018) - Unknown
No abstract available